'Citadels of spiritual resistance': the Italian schools in Scotland, 1924–1940. Issue 3 (24th August 2022) - Petrocelli, Remigio
Abstract: This article focuses on Italian schools in Scotland during the Fascist ventennio . The Italian-Scottish case study will be helpful to understand one of the principal means, the schools, that the Fascist regime used from the early 1920s in order to preserve the Italian identity of second-generation Italians. From the first half of the 1930s, the schools also became one of the key channels for spreading Fascist ideology and propaganda. Nevertheless, in Scotland, the schools also had a social significance, as Italians began to gather and socialise through them as a community. Accordingly, the foundations and educational, social and political roles of the schools will be examined. The article offers an insight into a topic neglected by Italian and British scholars, despite the second biggest Italian diasporic community in Britain residing in interwar Glasgow.